Optimasi formula dan evaluasi stabilitas fisik sediaan tablet effervescent ekstrak aqueous daun kelor (Moringa oleifera L.) - Benazir Evita Rukaya; Syuhada Syuhada; Devy Yulia Veronika (Journal Borneo, 2022)
Moringa leaves (Moringa oleifera L.) are a plant that is widely consumed by Indonesian people and has high nutrition and antioxidants. Utilization of Moringa leaves as a health supplement requires an innovative dosage form to make it practical to use, one of which is by making it in the form of effervescent tablets. The purpose of this study was to obtain an optimal formula for effervescent tablets of aqueous extract of Moringa leaves (Moringa oleifera L.). This study was an experimental study, by preparing effervescent tablets of aqueous extract of Moringa leaves using 3 different formulas using the wet granulation method. The physical stability of the effervescent tablets obtained was then evaluated. The evaluation results were analyzed to obtain the optimal formula from the 3 formulas. The research results obtained showed that F3 was a formula that had good physical stability of granules and tablets. Granules from F3 have an angle of repose of 22.45°, and a compressibility percentage of 12.67%. F3 effervescent tablets have a weight uniformity that does not exceed 5% or 10%, size uniformity that is not more than 3 times the thickness of the tablet, and a faster dissolving time compared to other formulas, namely 1 minute 22 seconds. Based on these results, it can be concluded that the optimal formula of the 3 formulas is F3 with an acid and base concentration of 20% each.